A novel non-invasive murine model for rapidly testing drug activity via inhalation administration against Mycobacterium tuberculosis - Xirong Tian; Xirong Tian; Xirong Tian; Xirong Tian; Yamin Gao; Yamin Gao; Yamin Gao; Yamin Gao; Chunyu Li; Chunyu Li; Chunyu Li; Chunyu Li; et al. (Frontiers in Pharmacology)
The efficacy of many compounds against Mycobacterium tuberculosis is often limited when administered via conventional oral or injection routes due to suboptimal pharmacokinetic characteristics. Inhalation-based delivery methods have been investigated to achieve high local therapeutic doses in the lungs. However, previous models, typically employing wild-type M. tuberculosis strains, were intricate, time-consuming, labor-intensive, and with poor reproducibility. In this study, we developed an autoluminescence-based inhalation administration model to evaluate drug activity by quantifying relative light units (RLUs) emitted from live mice infected with autoluminescent M. tuberculosis. This novel approach offers several advantages: (1) it eliminates the need for anesthesia in mice during administration and simplifies the instrument manipulation; (2) it is cost-effective by utilizing mice instead of larger animals; (3) it shortens the time from several months to 16 or 17 days for obtaining result; (4) it is non-invasive by directly measuring the live RLUs of mice as a surrogate marker for colony-forming units for in vivo drug activity testing; (5) up to six mice can be administrated daily and simultaneously, even 2–3 times/day; (6) results are relatively objective and reproducible results minimizing human factors. Proof-of-concept experiments demonstrated that inhalable rifampicin, isoniazid, and ethambutol showed anti-M. tuberculosis activity at concentrations as low as 0.5, 0.5, and 0.625 mg/mL, respectively, as evidenced by comparing the live RLUs of mice. Furthermore, consistency between RLUs and colony-forming units of the autoluminescent M. tuberculosis in lungs reaffirms the reliability of RLUs as an indicator of drug efficacy, highlighting the potential of this approach for accurately assessing anti-M. tuberculosis activity in vivo. This autoluminescence-based, non-invasive inhalation model offers a substantial reduction in the time, effort, and cost required for evaluating the efficacy of screening new drugs and repurposing old drugs in vivo via inhalation administration.